Effect of different types of recovery on blood lactate removal after maximum exercise - Ferreira, J. C.; da Silva Carvalho, R. G.; Moreira Barroso, T.; Szmuchrowski, L. A.; Sledziewski, D. (Polish Journal of Sport and Tourism, 2011)
Introduction. Despite physiological changes caused by immersion in liquid medium, few studies have been conducted to determine the kinetics of blood lactate removal under these conditions. The aim of this study was to verify the effect of active recovery, using a specific water bike, on the blood lactate concentration after maximum intensity exercise. Material and method. Ten healthy cycling athletes performed an Anaerobic Threshold Test by Heart Rate (HR) on a bicycle ergometer and an Anaerobic Threshold Test by Subjective Effort Perception on an aquatic bicycle ergometer. Three maximal test was performed immediately before each recovery type, in three different days: Passive Recovery on Land - PRL (horizontal position for 60 minutes), Passive Recovery in the Water - PRW (horizontal position, with the help of floats, in swimming pool for 60 minutes) and Active Recovery in the Water - ARW (the volunteer performed exercises on a water bicycle to an intensity corresponding to 85% of the intensity of LA in water, for 30 minutes, and remained in the same position of the PRW for another 30 minutes). Blood samples were collected 5, 15, 30 and 60 minutes after the maximal test, for lactate analysis. Results. The [La] blood did not show the difference between the three types of recovery at 5th min. From 15th min on, the difference between the ARW and the other two types of passive recovery was significant, and the ARW showed lower values. There was no significant difference between the PRW and PRL. Conclusion. Mere immersion in water is not enough to maximize the removal of blood lactate. This study demonstrates that active recovery held in water is effective for the removal of blood lactate in cyclists.